The Critical Theory of Robert W. Cox Fugitive or Guru? - Leysens, A. (International Political Economy Series, 2008)
This book, some 20 years after the publication of Robert W. Cox's seminal Production, Power and World Order: Social Forces in the Making of History , offers the reader an analytical and comprehensive overview of his work and illustrates the continuing relevance thereof for contemporary research.